3D Simulation of the Filtration and Dust Retention Process of a Fuel Filter. Issue 8 (7th July 2015) - Valiño, Luis; Mustata, Radu; Hierro, Juan; Hernández, Juan L.; Busack, Martin; García, Maria J.; Blasco, Carlos
Abstract A model for the description of the dust retention process inside a filter was developed and successfully applied to a detailed 3D numerical simulation of a Bosch automotive diesel filter. Specifically, the variation of the pressure drop due to the clogging process in the filter paper could be well predicted. For this approach, an Eulerian‐Eulerian two‐phase flow formulation was applied. For the dispersed phase, the Eulerian description was made by means of a probability density function transport equation. The simulations also provide complete spatial information about the flow both in the clean and dirty sides of the filter and the particle distribution, size, and velocity. The intention of the newly developed numerical tool is to help in the design of filtering devices.